Control techniques for a Three Phase Four Wire (3P4W) Shunt Energetic Power Filter - Dr.S. Jayalakshmi; Dr.K.Venkatasubramanian; Sri. Sk. Sadik Basha; Smt. K. Sireesha; M. Venu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In this research, we provide a novel model of control for a 3P4W shunt energetic power filter. Typically, a power electronics device's control method will have two control loops: a fastresponding inner current loop and a more gradualresponding outer voltage loop. Because of the dynamic loop of the cirrent, the PI regulator cannot monitor it. The repetitive controllers (RC), which offer excellent gain at all frequencies, are widely recognised for their capacity to follow periodic signals. The higher frequency range's strong gain could cause instability. As a result, the sensitivity function of the regular RC is squared in the proposed study. This project uses a fuzzy logic controller to improve the power quality. This method provides a sensitivity function with a moderate amplitude while giving deep notches at low to medium frequencies and with more frequency low notches. This control approach has been tested and put into practise on the 3P4W SAPF.